2020
DOI: 10.3389/fbioe.2019.00439
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of Methylation and Transcriptome Identified Epigenetically Regulated lncRNAs With Prognostic Relevance for Thyroid Cancer

Abstract: Emerging evidence has shown that epigenetic changes in DNA methylation, an important regulator of long non-coding RNA (lncRNA) expression, can disturb the expression patterns of lncRNAs and contribute to carcinogenesis. However, knowledge about crosstalk effects between DNA methylation and lncRNA regulation in thyroid cancer (THCA) remain largely unknown. In this study, we performed an integrated analysis of methylation and the transcriptome and identified 483 epigenetically regulated lncRNAs (EpilncRNAs) asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer. This fits with the growing body of research showing that lncRNAs and other non-coding RNAs play a key role in cancer [30,31,32].…”
Section: Discussionsupporting
confidence: 82%
“…Additionally, we showed that our gene lists contain many non-coding RNA genes, primarily consisting of lncRNAs, suggesting that methylation alterations at non-coding gene promoters are frequently present in cancer. This fits with the growing body of research showing that lncRNAs and other non-coding RNAs play a key role in cancer [30,31,32].…”
Section: Discussionsupporting
confidence: 82%
“…These predicted epigenetically regulated lncRNAs in this study would provide an available resource for studying the interplay between lncRNAs and epigenetic regulation. A recent study performed by Li et al (2019) has characterized the crosstalk between DNA methylation and lncRNA expression in thyroid Cancer (THCA) and methylation-driven 5-lncRNA-based signature (EpiLncPM) with potential clinical application in predicting the prognosis of THCA. Therefore, to further investigate whether epigenetically regulated lncRNAs identified here also have potential clinical value, we performed univariate Cox regression analysis with OS and found that only 17 of 419 epigenetically regulated lncRNAs identified here were significantly associated with patients’ outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Dysregulated lncRNAs have been observed in various cancers and have also been implicated as novel biomarkers in cancer diagnosis, prognosis, and therapeutic response ( Zhou et al, 2016a , 2020 ; Hosseini et al, 2017 ; Huo et al, 2017 ; Tian et al, 2018 ; Bao et al, 2020 ; Sun et al, 2020 ). Previous studies have reported that the expression of some lncRNAs can be regulated by epigenetic modification similar to protein-coding genes ( Zhao et al, 2015 ; Wang et al, 2018 ; Li et al, 2019 ). However, the epigenetically regulated lncRNAs and their association with clinical outcome and therapeutic response in OV remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies found that aberrant expression of lncRNAs could be caused by altered DNA methylation contributing to carcinogenesis. The relationship between epigenetic alterations and lncRNAs expression has been revealed in several cancers ( Hadji et al, 2016 ; Li et al, 2019 ; Zhang et al, 2019 ; Hou et al, 2020 ; Zhang et al, 2020 ). However, epigenetically dysregulated lncRNAs and their functional and clinical roles in Head and Neck Squamous Cell Carcinoma (HNSCC) are still not explored.…”
Section: Introductionmentioning
confidence: 99%